Incompatibility of Slovenian Regulations in the Field of Water Management with European Regulations and Resulting Damage - Mario Krzyk; Darko Drev (LeXonomica, 2021)
The issue of water management in Slovenia is regulated by several laws and by-laws. The right to drinking water is enshrined in the Constitution of the Republic of Slovenia. Individual by-laws in the field of water management are not coordinated with higher-level laws, the Constitution of the Republic of Slovenia, nor with EU regulations (directives, regulations). There are no relevant provisions in laws and by-laws that would enforce the right to drinking water enshrined in the Constitution. A major problem exists in the field of wastewater disposal and treatment, water protection, flood safety, etc. An even bigger problem, such as inconsistencies in regulations, is their poor implementation. This leads to excessive pollution and great material damage as well.Povzetek. Upravljanje z vodami v Sloveniji ureja več zakonov in podzakonskih aktov. Pravica do pitne vode je zapisana v Ustavi Republike Slovenije. Posamezni podzakonski akti s področja upravljanja z vodami niso usklajeni z zakoni višje stopnje, z Ustavo Republike Slovenije, niti s predpisi EU (direktive, uredbe). V zakonih in podzakonskih aktih ni ustreznih določb, ki bi uveljavljale pravico do pitne vode, zapisano v ustavi. Velik problem obstaja na področju odvajanja in čiščenja odpadnih voda, varstva voda, poplavne varnosti itd. Še večji problem, kot so nedoslednosti v predpisih, je njihovo slabo izvajanje. To povzroča prekomerno onesnaževanje in tudi veliko materialno škodo.